“A Total Black Hole”: How COVID-19 Increased Bureaucratic Violence Against Refugees in Greece - Raluca Bejan; Tracy Glynn (Refuge, 2024)
State responses to COVID-19 were unevenly felt across society. Negative consequences of lockdowns and travel restrictions for the upper classes were largely restricted to not seeing friends or taking holidays. For those with little or no right to have rights (Arendt, 1970), those relegated to society’s margins—such as refugees and asylum claimants—state responses to COVID-19 metamorphosed into Kafkaesque restrictions, surveillance, and control. Informed by participant observations and 10 interviews with civil society actors conducted in Athens in 2021 and 2022 at the height of the pandemic, this paper shows how the Greek state weaponized COVID-19 to further exclude refugees from society, deny asylum procedures, and reduce service provision for those awaiting the outcome of their asylum claims.